Frugal Innovation for the BoP in Brazil – An Analysis and Comparison with Asian Lead Markets - Wimschneider, Christine; Agarwal, Nivedita; Brem, Alexander (International Journal of Technology Management, 2020)
In recent years, frugal innovation and its antecedents have gained significant attention in both theory and practice. However, the vast majority of research focuses mainly on China and India and their bottom of the pyramid (BoP) customers. Against this background, our research investigates frugal innovation and its reception in Brazil. We analyse six Brazilian company cases (three multinational corporations and three small- and medium-sized enterprises) in terms of frugal product development, product characteristics, and commercialisation approaches, as well as compare these organisations with findings from Asian lead markets. Our results confirm that the principal dimensions of frugal innovation are cost-effectiveness and ease of use. However, the findings also contradict the paradigm that frugal innovation must be essentially low-cost. Based on these results, we propose a twofold approach to the cost criterion that differentiates between the companys and the customers perspective and focuses on value-based pricing. Further, distinctive product features, branding, and specific marketing activities are crucial for successful frugal innovation in Brazil. This research extends the classification of frugal innovation in prior literature and suggests understanding frugal dimensions as a set of building blocks that can be flexibly applied to frugal product development depending on the context and regional requirement
Keywords: BoP; Brazil; Emerging Markets; Frugal Innovation; Latin America; Product Development